Internet of things for industrial monitoring and control applications - A. Karthika, R; Rahamtula, Shaik; Anusha, Yalavarthi (International Journal of Engineering and Technology, 2018)
Smart enterprise is an observing, controlling and investigating carrier which incorporates wireless transmission generation and electronic sensor innovation. It permits the client to get the overall scope of services, the opportunity for continuous monitoring and automated controlling of industrial environment.Â  This paper was advanced to provide internet based totally smoke and temperature and security tracking. This device is allowed to track the facts every time & everywhere from the source of the internet whenever we login into internet. This paper also concludes that person can set restriction for above parameters & if these parameters cross beyond that cost, it's going to activate the devices. As a part of its alarm gadget, it'll play the recorded sounds: â€œintruderâ€ or â€œsmoke detectedâ€ when there may be a detection. The credit score card size Raspberry Pi (RPI) with Open source pc vision (OpenCV) software program handles the photo processing, control algorithms for the alarms and sends captured snap shots to consumerâ€™s e mail through wireless. In this project Raspberry Pi3B+ is used.Â Â